Atypical ERP responses to audiovisual speech integration and sensory responsiveness in infants at risk for autism spectrum disorder. (17th January 2022) - Riva, Valentina; Riboldi, Elena Maria; Dondena, Chiara; Piazza, Caterina; Molteni, Massimo; Cantiani, Chiara
Abstract: Atypical sensory responses are included in the diagnostic criteria of autism spectrum disorder (ASD). Autistic individuals perform poorly during conditions that require integration across multiple sensory modalities such as audiovisual (AV) integration. Previous research investigated neural processing of AV integration in infancy. Yet, this has never been studied in infants at higher likelihood of later ASD (HR) using neurophysiological (EEG/ERP) techniques. In this study, we investigated whether ERP measures of AV integration differentiate HR infants from low‐risk (LR) infants and whether early AV integration abilities are associated with clinical measures of sensory responsiveness. At age 12 months, AV integration in HR ( n = 21) and LR infants ( n = 19) was characterized in a novel ERP paradigm measuring the McGurk effect, and clinical measures of sensory responsiveness were evaluated. Different brain responses over the left temporal area emerge between HR and LR infants, specifically when AV stimuli cannot be integrated into a fusible percept. Furthermore, ERP responses related to integration of AV incongruent stimuli were found to be associated with sensory responsiveness, with reduced effects of AV incongruency being associated with reduced sensory reactivity. These data suggest that early identification of AV deficits may pave the way to innovative therapeutic strategies for the autistic symptomatology. Further replications in independent cohorts are needed for generalizability of findings.